Some Challenges for the Teaching Profession - Piwowarski, Rafał (Multidisciplinary Journal of School Education, 2024)
Purpose and problems: The purpose of this article is to investigate some challenges for working teachers and to present selected issues that are not always known and understood, but which concern one of the key problems of education: the profession of teaching.Research methods: In this article, the “teacher” aspect is examined in a comparative context: from the perspective of social, economic and political conditions. For this purpose, methods of comparative analysis relating to a number of indicators and information from an international perspective are used (based on a critical choice of data from different studies). This helps clarify some relationships that can be found.Structure of the article: The article consists of three parts. The first part focusses on inclusive education (here limited mainly to the inclusion of culturally and linguistically diverse students). The second addresses the financing of education and the work of the teacher (with a focus on student performance against this background), whilst the third part covers issues such as digital transformation and scientific capital.Research findings and their impact on the development of educational sciences: The information and theses presented herein allow one to look at the teaching profession in a way that is less pedagogical and more political or social.Results/recommendations: Firstly, the paper shows that many teachers are not well-prepared to teach students from different ethnic backgrounds, speaking foreign languages etc. A second, somewhat more widely discussed point is that teachers generally earn less than workers with similar education. Furthermore, in some cases, it is not always more funding for education or higher salaries for teachers that result in better student performance. Thirdly, teachers should keep up with the digital transformation and teaching needs connected with science capital.